Faktor-faktor yang berpengaruh terhadap kelengkapan pengisian rekam medis pasien rawat inap dan pertanggungjawabannya secara hukum di RSUD Kabupaten Karimun - ADRINA, Frista ([Yogyakarta] : Universitas Gadjah Mada, 2009)
General Hospital Regency Karimun is C-Class hospital owned by Regency Karimun. As a health service unit, General Hospital Regency Karimun was demanded to improve quality of factors that influencing on completeness of registering medical record and weakness in making medical record, in example incomplete registration if there was unsatisfied patient, it could bring legal claim event. General Hospital Regency Karimun included hospital that supposed to have a feasibility. Therefore, if it was found that there was incomplete registration and medical record could be found when needed, it would be resistant if there was unsatisfied patient and do legal claim on hospital’s doctor. Because it was weak to prove the evidence. The objective of the research was to examine completeness of registering medical record in the hospitalizing patient and to identify factors that influencing completeness of registering medical record in the hospitalizing patient and the legal responsibility. Research design used was cross-sectional survey and research kind was descriptive using quantitative data and qualitative data, by studying completeness of registering medical record in the hospitalizing patient and to know doctor, nurse and medical record officer’s argument concerning factors that influencing completeness of registering medical record in the hospitalizing patient and the legal responsibility. Result of the research in General Hospital Regency Karimun concluded that there were still many incomplete hospitalizing medical record based on estimation of average complete treatment class of 28.6%. Implementation of registering medical record in the hospitalizing patient has not optimally been conducted yet. It was due to some factors including; less time, lazy and never claimed or having case, lack of awareness in officer, scarce medical officer, inefficient medical record and officer has not done a review and has not given a feedback. In this research, registering medical record in the hospitalizing patient at General Hospital Regency Karimun was about 28.6% in complete. If there was patient to claim, then both doctor or hospital’s management were weak in legal position, so that it was required some synergic efforts to improve them, including medical record training, notice, follow-up with regular feedback, giving reward and punishment, medical record system improvement, reactivation of medical record committee and do medical audit.